Assimetrias do contrato de concessão comercial entre produtores e distribuidores de veículos automotores de via terrestre - Martins, Sérgio Ludovico (2018)
The contractual celebration is a milestone in the expression of individual freedom. Private autonomy in the contractual scope is analyzed by the manifestation of the volitional element of the parties in comparison with the models of state intervention. The commercial concession agreement signed by automakers and dealers aims to regulate the dynamics of indirect distribution of motor vehicles, parts and services. The asymmetries of this contractual relationship are identified by the doctrine, Brazilian and foreign, for decades, including having motivated the edition of the Renato Ferrari Law. The intensification of competition in the national scenario, arising from the installation of new brands, has reduced the margin of profitability of the automotive segment. In this quadrant, the automakers began to carry out the closure of indirect distribution operations, regardless of the operating time, making possible the return of the capital invested by regional business groups. The asymmetry of the contractual link is expressed in the performance of the dominant firm, automakers, through the disproportionate increase in intra-brand competition, evasion of information and imposition of obligations, through internal communiqués devoid of contractual or negotiating ballast. In order to maintain the transfer to international headquarters, some automakers are imposing financial losses on indirect distributors through the stocking of products, considering the incidence of financial charges in the current account opened by the related floor plan contract. Public interest militates for the prohibition of holk-back and similar programs, with fictitious values being released to the invoices of invoicing new vehicles, considering the financial losses imposed on the dealers and the mockery to the due collection of taxes. The contractual asymmetries cause financial losses to business groups mostly of Brazilian capital, loss of capacity for development of the national economy, and worsening consumer service. The modernization of state intervention directs the prohibition of the stocking of products to the detriment of dealers, objective criteria for expanding intra-brand competition and restricting the relevance of internal communiqués issued by the automakers